2020
DOI: 10.5114/aoms.2019.89218
|View full text |Cite
|
Sign up to set email alerts
|

Association of masked uncontrolled hypertension and cardiovascular diseases in treated hypertensive patients

Abstract: The aim of the study was to evaluate the association of masked uncontrolled hypertension (MUCH) and prevalence of cardiovascular disease in treated hypertensive patients. Material and methods: Patients' demographics and prior medical histories were collected. Fasting venous blood was drawn for evaluation of serum creatinine level, which was used to calculate glomerular filtration rate (GFR). Clinic blood pressure (BP) and 24 h ambulatory blood pressure monitoring (ABPM) measurements were performed. Based on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 43 publications
(38 reference statements)
1
11
0
1
Order By: Relevance
“…Prior studies have reported MHT to be associated with a higher prevalence of LVMI and LVH compared with sustained normotension [19,21–23]. Moreover, studies have reported that masked uncontrolled hypertension is associated with increased CVD risk [18,24]. These studies have used awake BP and BP thresholds consistent with the JNC7 guideline to define high out-of-office BP.…”
Section: Discussionmentioning
confidence: 99%
“…Prior studies have reported MHT to be associated with a higher prevalence of LVMI and LVH compared with sustained normotension [19,21–23]. Moreover, studies have reported that masked uncontrolled hypertension is associated with increased CVD risk [18,24]. These studies have used awake BP and BP thresholds consistent with the JNC7 guideline to define high out-of-office BP.…”
Section: Discussionmentioning
confidence: 99%
“…Vascular amyloidosis caused by the deposition of MFG-E8 and medin is also involved in the pathogenesis and progression of arterial hypertension, which may be mediated by the interaction between MFG-E8 (medin) and the cells within the layers of the arterial wall. For example, the endothelial dysfunction during amyloidosis leads directly to hypertension, with the decrease in nitric oxide resulting in impaired endothelium-dependent vasodilation [31,32]. The VSMCs also shift their phenotypes during the whole amyloidosis process, which ultimately leads to increased vascular wall stiffening, with decreased elasticity and subsequent hypertension [33].…”
Section: Medin Amyloidosis and Hypertensionmentioning
confidence: 99%
“…Although, medical treatment is a first line management in patients with renovascular hypertension [4], recent population-based data show that blood lowering therapy is insufficient in about 30% of hypertensive patients leading to masked uncontrolled blood pressure elevations [7]. This blood pressure instability is most frequent in patients with cardiovascular comorbidities, and those who require multiple antihypertensive medications [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Although, systolic (SBP) and diastolic blood pressure (DBP) lowering following PTA for ARAS is associated with better outcomes, the effect of PTA on blood pressure response is difficult to predict [9,10]. For example randomized trials demonstrate mild or no advantage of PTA plus best medical therapy (BMT) over BMT alone in regard to blood pressure or renal function improvement in all-comers with ARAS [6,7,8,12]. On the other hand, observational studies reported potential advantage of PTA of ARAS in terms of cardiovascular death (CVD) and all-cause mortality risk decrease, blood pressure lowering or even hypertension cure [13,14,15].…”
Section: Introductionmentioning
confidence: 99%